2005
DOI: 10.1128/mcb.25.20.8904-8912.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nonconventional Involvement of LysRS in the Molecular Mechanism of USF2 Transcriptional Activity in FcεRI-Activated Mast Cells

Abstract: Reports of the biological multifunctional activity of various aminoacyl tRNA synthetases have recently accumulated in the literature. The primary function of these critical enzymes is to charge various tRNAs with their appropriate amino acids, thus producing the building blocks of protein synthesis. We have previously shown that lysyl tRNA synthetase (LysRS) associates with microphthalmia transcription factor (MITF) and regulates its activity by synthesis of Ap 4 A in mast cells. Here, we show for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 45 publications
(62 reference statements)
5
69
0
Order By: Relevance
“…Thus, in mast cells, HINT1 inhibits the activities of the bHLH transcription factors MITF and USF2 by binding directly to these proteins (16,17), and in SW480 cells, HINT1 inhibits h-catenin/TCF4 activity by binding to the associated proteins Pontin and Reptin (18). The latter study also found that because of this effect, HINT1 also inhibits the transcription of cyclin D1 and expression of the cyclin D1 protein (18).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, in mast cells, HINT1 inhibits the activities of the bHLH transcription factors MITF and USF2 by binding directly to these proteins (16,17), and in SW480 cells, HINT1 inhibits h-catenin/TCF4 activity by binding to the associated proteins Pontin and Reptin (18). The latter study also found that because of this effect, HINT1 also inhibits the transcription of cyclin D1 and expression of the cyclin D1 protein (18).…”
Section: Discussionsupporting
confidence: 57%
“…Since then, other investigators have obtained evidence that the HINT1 protein can also interact with other proteins, which include the product of the ATDC gene (13), which seems to play a role in cellular responses to ionizing radiation; cyclin-dependent kinase 7 (14), which functions in growth control and transcriptional regulation; the human mu-opioid receptor, which is a Gprotein-coupled receptor that mediates analgesia, euphoria, and other important central and peripheral neurologic functions (15); the transcription factor microphthalmia also called MITF (16), which plays an important role in mast cell and melanocyte growth; the ubiquitously expressed transcription factor USF2 (17); and Pontin and Reptin (18), which complex with h-catenin and thereby regulate the h-catenin/TCF4 signaling pathway. Indeed, the latter study indicated that overexpression of HINT1 significantly inhibited both h-catenin/TCF4 and cyclin D1 transcription factor activity in SW480 colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that both MITF and another bHLH-Zip transcription factor, upstream stimulatory factor 2 (USF2) form a tertiary complex with their inhibitor histidine triad nucleotide-binding 1 (Hint-1) and with lysyl-tRNA synthetase (LysRS) (16,17). Furthermore, we have shown that Ap 4 A can bind to Hint-1 and cause its release from MITF and from USF2 (16,17).…”
mentioning
confidence: 95%
“…Hint1 has also been associated with transcription factors such as, TFIIH (11), MITF (12,13), and USF2 (14). In addition, the interactions between MITF and USF2 appear to be mediated by LysRS (13)(14)(15).…”
mentioning
confidence: 99%